Examining the performance of DoD and PoD portfolios and determinants in developed and developing countries / Siti Hajar Nadrah Mohamad Ghouse - Mohamad Ghouse, Siti Hajar Nadrah (Institute of Graduate Studies, UiTM, 2018)
Believers of the Efficient Market Hypothesis have argued that it is impossible to make abnormal return since market is efficient. Nevertheless, the contrarian strategists differ to agree. In this setting, this study attempts to examine the ability of Dogs of the Dow (DoD) and Puppies of the Dow (PoD) trading strategies in outperforming the market return. The analyses are done on the DoD and PoD portfolios of 15 individual countries and as well as a group. In addition, this study also investigates determinants (dividend yield, size, gross domestic product and inflation rate) that might affect the returns of these DoD and PoD portfolios. The countries studied are Australia, Hong Kong, Japan, New Zealand, Singapore, South Korea and Taiwan for developed countries and Brazil, Russia, India, China, South Africa, Malaysia, Indonesia and Thailand for developing countries. Yearly data comprising of return, dividend yield, size, gross domestic product and inflation rate are collected from 2000 until 2014. Empirical findings reveal that DoD portfolios outperformed the market in all 15 individual countries studied but the results are only statistically significant in the Russian market. However, when analysis was done as a group, the portfolio returns of DoD beat the market statistically and significantly for developed and developing countries. As for the PoD portfolios, the results indicate that abnormal returns are statistically significant only in share markets of New Zealand, Taiwan and Russia. Similar to the results of DoD portfolios, PoD portfolios also outperformed the share market in the respective countries as a group and these abnormal returns are also statistically significant…